ARTIST'S ROLE IN STRENGTHENING INDONESIA'S NATIONAL DEFENSE (DEFENSE SOCIOLOGY STUDIES IN A DIGITAL SOCIETY) - Bartoven Vivit Nurdin; Sindi Utami; Damar Wibisono; Ifaty Fadliliana Sari (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
The sense of nationalism in citizens of Indonesia has been degraded along with the influence of globalization and digitalization, which also has implications for the decreasing awareness of State Defense. The Ministry of Defense of the Republic of Indonesia has carried out innovation by launching the 'Ngopi (Ngobrol Pintar) Daring Bela Negara' or Online Smart Talk in State Defense program a breakthrough from this program is to make artists a model for defending the country. Artists are figures who are close to social media and digital society. This study aims to analyze the artist as a symbol of national defense. This study uses the grand theory from Karl Marx and the main theory about symbolic interpretation by Geertz (1973). This study uses a qualitative approach and data collection techniques with in-depth interviews and observations. The study results show that artists were chosen to be models in the program because artists are seen as symbols that have meaning in building a sense of nationalism, especially for the younger generation in today's digital society. Artists have a significant role in influencing people's attitudes and behavior, especially the younger generation, in fostering a sense of nationalism which currently tends to access a lot of social media. These artists define Defending the Country according to their achievements in their respective fields of expertise so that the digital community feels motivated and moved to participate in spreading the spirit and values of Defending the Country. This program is considered to provide a different color and is successful enough to be held on an ongoing basis.